Impacto de alimentos ultraprocessados no corpo de ribeirinhos do Médio Solimões, Amazonas - SANTOS, Alessandra Carvalho dos (2023)
This work aims to evaluate the nutritional status of the adult population of riverside dwellers from the Middle Solimões in Amazonas and the food consumption in terms of the type of processing used in its production. The research participants are riverside dwellers from the Middle Solimões, Amazonas, living off fishing and subsistence agriculture. This study was carried out through the analysis of feeding through 24-hour recall, carried out for five days in a row in the dry season of the year (October to December) 2015. The recalls were made individually with a couple (man and woman) with ages between 18 and 49 years. The sample used in the work is composed of 36 households, including 36 men and 36 women. The statistical treatment of the data consisted of the chisquare and Pearson correlation tests, carried out on the “Social Science Statistic” website. The results showed high consumption values of ultra- processed and urban foods. There was a significant correlation between the Body Mass Index and Subscapular Skin Fold with the consumption of ultra-processed foods. In conclusion, the transformation of the eating habits of the riverside population, generating the increasing presence of ultraprocessed and urban foods, which ultimately end up interfering with the nutritional health of the population studied.